PENDIDIKAN KARAKTER DI SEKOLAH UPAYA MEMBANGUN KARAKTER BANGSA - Ali Muttaqin (LPPM Institut Agama Islam Al-Hikmah Tuban, 2012)
emergence of a national movement of character education in formal educational institutions, announced the Ministry of National Education in 2010, is the government's response to the condition of the nation which in the past decade is getting worse and weaker confidence as a nation great and dignified, as well as efforts to build human Indonesia is knowledgeable, has a high reasoning power, creative, innovative, virtuous and noble. The nation collapsed and weakened its confidence as a result of various actions are not commendable, among others: the many acts of corruption, collusion and abuse of office or authority by some state officials; moral crisis and moral people, especially students and teenagers who are very concerned, as proliferation of mass fights, wild race, drugs party, free sex, murder, suicide, other immoral acts, and the poor quality of our national education when compared with neighboring countries in Asia. The education process has been more oriented towards the development of cognitive (left brain) which aims to equip students with knowledge (intellect) as much as possible, and not enough on character development (right brain) associated with the morals and spirituality of children. Of such educational practices, human beings are born smart and intellectually, but spiritual or moral crisis or uncharacterized, as happens in the reality of people's lives today. Therefore, necessary to develop character education in schools, because school or madrasah is a strategic place to design the character and improve the quality of life, so that children in speech, attitude and behavior must reflect good character. This paper seeks describes the idea of the importance of character education in formal educational institutions such as schools and Madrasah in an effort to build the nation's character. Some fundamental problems are solved in this paper is whether the need for character education reasons, how the reality of education today, how the conception of the character and purpose of that character education, as well as how to approach and design character education in schools. This study uses the approach of Islamic education, and hence his presentation much use terms commonly used in Islamic education.